Coagulopathy and hemostasis management in patients undergoing liver transplantation: Defining a dynamic spectrum across phases of care. Issue 10 (13th May 2022) - Pillai, Anjana A.; Kriss, Michael; Al‐Adra, David P.; Chadha, Ryan M.; Cushing, Melissa M.; Farsad, Khashayar; Fortune, Brett E.; Hess, Aaron S.; Lewandowski, Robert; Nadim, Mitra K.; Nydam, Trevor; Sharma, Pratima; et al.
Abstract: Patients with acute and chronic liver disease present with a wide range of disease states and severity that may require liver transplantation (LT). Physiologic alterations occur that are dynamic throughout all phases of perioperative care, creating complex management scenarios that necessitate multidisciplinary clinical care. Specifically, alterations in hemostasis in liver disease can be pronounced and evolve with disease progression over time. Recent studies and society guidance address this emerging paradigm and offer recommendations to assist with hemostatic management in patients with liver disease. However, patients undergoing LT are unique and diverse, often with unstable disease that requires specialized approaches. Our aim is to provide a focused review of hemostatic management of the LT patient, distinguish unique aspects of the three main phases of care (before LT, perioperative, and after LT), and identify knowledge gaps and critical areas of future research.